Synthesis, structural study, antimicrobial activity and theoretical treatment of Cr(III), Ni(II), Pt(IV) and Zn(II) complexes with 2-hydroxy-4-Nitro phenyl piperonalidene (Baghdad Science Journal, 2025)
The complexes of the 2-hydroxy-4-Nitro phenyl piperonalidene with metal ions Cr(III), Ni(II), Pt(IV) and Zn(II) were prepared in ethanolic solution. These complexes were characterized by spectroscopic methods, conductivity, metal analyses and magnetic moment measurements. The nature of the complexes formed in ethanolic solution was study following the molar ratio method. From the spectral studies, monomer structures proposed for the nickel (II) and Zinc (II) complexes while dimeric structures for the chromium (III) and platinum (IV) were proposed. Octahedral geometry was suggested for all prepared complexes except zinc (II) has tetrahedral geometry, Structural geometries of these compounds were also suggested in gas phase by using hyper chem-8 program for the molecular mechanics and semi-empirical calculations. The heat of formation and binding energy for the prepared compounds was calculated by using PM3 and AMBER methods. The method of PM3 was used for evaluate the vibration spectra for the imine and starting material as authentic compound. Preliminary in vitro tests for antibacterial and antifungal activity show that most of the prepared compounds display good activity to (Staphylococcus aureus), (Escherichia coli) and (Candida albicans).